2020
DOI: 10.3892/mco.2020.2091
|View full text |Cite
|
Sign up to set email alerts
|

Historical retrospective of the SRC oncogene and new perspectives (Review)

Abstract: Since its first discovery as part of the Rous sarcoma virus (RSV) genome, the c-SRC (SRC) proto-oncogene has been proved a key regulator of cancer development and progression, and thus it has been highlighted as an attractive target for anti-cancer therapeutic strategies. Though the exact mechanisms of its action are still not fully understood, SRC protein mediates crucial normal cell functions, such as cell development, proliferation and survival, and its dysregulation is considered as an oncogenic signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 105 publications
0
25
0
Order By: Relevance
“…A recent study reported that TRIM7 targets the proto-oncogene Src for lys48-linked polyubiquitination and degradation (Zhu et al, 2020). Moreover, Src plays an important role in the regulation of HIF-1α levels (Chou et al, 2010; Lee et al, 2011;Simatou et al, 2020). Thus, we investigated whether TRIM7 regulates HIF-1α signaling by targeting Src.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that TRIM7 targets the proto-oncogene Src for lys48-linked polyubiquitination and degradation (Zhu et al, 2020). Moreover, Src plays an important role in the regulation of HIF-1α levels (Chou et al, 2010; Lee et al, 2011;Simatou et al, 2020). Thus, we investigated whether TRIM7 regulates HIF-1α signaling by targeting Src.…”
Section: Discussionmentioning
confidence: 99%
“…The proto-oncogene Src is a non-receptor tyrosine kinase that regulates a wide range of cellular events, including cell growth, differentiation, proliferation, survival, adhesion, migration, and motility (Simatou et al, 2020). In normal cells, Src is strictly regulated at both the transcriptional and post-translational levels by a variety of mechanisms.…”
Section: Cell Ell B Biology Iology I International Nternationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, tumor viruses can control the complex genome of host cells, promoting unrestricted cell proliferation (13)(14)(15). Experiments on induction of chicken sarcoma by Rous virus demonstrate that virus infection can successfully induce tumor formation (16,17), showing that tumors can either develop spontaneously in organisms or be formed by virus induction. The above observation has laid a foundation for the following in vitro tumor cell cultures and in vivo transfection in mice.…”
Section: Tumor Virusesmentioning
confidence: 99%
“…The above observation has laid a foundation for the following in vitro tumor cell cultures and in vivo transfection in mice. It has been shown that infection of Rous virus leads to the occurrence of tumor cell traits in the cultured cells in vitro, which include a loss of contact inhibition, continued proliferation and anchoring independence (17). To date, several tumor viruses have been identified, including human herpes virus 8 (HHV-8) (18)(19)(20), human papilloma virus (HPV) (19,(21)(22)(23)(24)(25)(26)(27), hepatitis B virus (HBV) (19,(28)(29)(30), Epstein-Barr virus (EBV) (19,26,(31)(32)(33)(34)(35), Cytomegalovirus (CMV) (19,27,(36)(37)(38), human immunodeficiency virus (HIV) (19,(39)(40)(41)(42), human T cell lymphotropic virus (HTLV) (43,44) and hepatitis C virus (HCV) (45)(46)(47)(48) (Fig.…”
Section: Tumor Virusesmentioning
confidence: 99%